Tetrabromobisphenol A in Indoor Dust from Houses and Internet Cafes - Espino, Ma. Pythias B.; Leon, Jessica N. (Science Diliman: A Journal of Pure and Applied Sciences, 2012)
Tetrabromobisphenol A or TBBPA is a widely used brominated flame retardant in modern materials such as electronic products, plastics and building materials. TBBPA can leach out of flame retardant-treated products during production, use, reuse, and final disposal of these consumer products. It has thus become a contemporary environmental contaminant. This study reports the levels of TBBPA in indoor dust from houses (n=4) and internet cafes (n=5) in Angono and Quezon City, in the Philippines. TBBPA in indoor dust was analyzed by ultrasonication-assisted hexane extraction and HPLC-UV determination. The instrument and method detection limits were 0.004 ng uL-1 and 1275 ng g-1, respectively. The standard calibration solutions ranged from 0.03 to 0.30 ng uL-1 (r2=0.9956). The extraction recovery was 78% (n=3. TBBPA was found in six of the nine indoor dust samples studied where the concentrations ranged from not detected to 4916 ng g-1. The occurrence and levels of TBBPA in indoor dusts are significant and suggest the need for further investigations especially in other microenvironments where people may be exposed to this contaminant.
Keywords: tetrabromobisphenol A, indoor dust, ultrasonication, HPLC-UV